1983
DOI: 10.1002/macp.1983.021840122
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of polydisperse polyethylene fractionated according to pennings' method

Abstract: It is shown that the molten state and the semi-crystalline state of polydisperse polyethylene are interrelated. Large polydisperse fractions obtained according to Pennings' fractionation method were studied by small angle X-ray scattering and differential thermal analysis; the long period, depending on the molecular weight distribution, is shown to be given by the weight average end-to-end distance of the coils; the long chains with molecular weights M > lo5 behave as a series of "sub-chains" with molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The C, value is usually lower than C,z (see for example [10,11,17]). This is due to the fact that C,1 is related to the alternate crystalline and amorphous regions and this value does not take into consideration the interspherulitic amorphous phase and the defects in crystalline lamellae.…”
Section: First Process Of Polymer Chain Scissionmentioning
confidence: 98%
“…The C, value is usually lower than C,z (see for example [10,11,17]). This is due to the fact that C,1 is related to the alternate crystalline and amorphous regions and this value does not take into consideration the interspherulitic amorphous phase and the defects in crystalline lamellae.…”
Section: First Process Of Polymer Chain Scissionmentioning
confidence: 98%
“…Eda et al We raise two questions: Why are the mobilities of the two kinds of peroxy radicals trapped in the crystalline sites different and why do the mobile peroxy radicals abstract hydrogen intermolecularly. 3 In order to answer these 0024-9297/85/2218-0170$01.50/0 questions, one must acquire a knowledge of the surrounding conditions of the peroxy radicals, for instance, the molecular orientations of the polymer chain and the conformational structures of the radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In ref 1, the long periods of polydisperse polyethylene (PE) of various molecular weight distributions were measured. It has been shown that there is no general law between L and Mw but that for low molecular weight material, L can be expressed as a function of Afn according to the relation L s Afn1/2 for Afn < 105 (2) regardless of the value of Afw. In that case it can be concluded that the long period is given principally by the end-to-end distance r of the coils having the molecular weight Ain.…”
Section: Introductionmentioning
confidence: 99%